Clinical Profiles of Multidrug-Resistant and Rifampicin-Monoresistant Tuberculosis in Korea, 2018–2021: A Nationwide Cross-Sectional Study - Jinsoo Min; Yousang Ko; Hyung Woo Kim; Hyeon-Kyoung Koo; Jee Youn Oh; Doosoo Jeon; Taehoon Lee; Young-Chul Kim; Sung Chul Lim; Sung Soon Lee; Jae Seuk Park; Ju Sang Kim (Tuberculosis and Respiratory Diseases)
Background This study aimed to identify the clinical characteristics of multidrug-resistant/rifampicin-resistant tuberculosis (MDR/RR-TB) in the Republic of Korea. Methods Data of notified people with tuberculosis between July 2018 and December 2021 were retrieved from the Korea Tuberculosis Cohort database. MDR/RR-TB was further categorized according to isoniazid susceptibility as follows: multidrug-resistant tuberculosis (MDR-TB), rifampicin-monoresistant tuberculosis (RMR-TB), and RR-TB if susceptibility to isoniazid was unknown. Multivariable logistic regression analysis was conducted to identify the factors associated with MDR/RR-TB. Results Between 2018 and 2021, the proportion of MDR/RR-TB cases among all TB cases and TB cases with known drug susceptibility test results was 2.1% (502/24,447). The proportions of MDR/RR-TB and MDR-TB cases among TB cases with known drug susceptibility test results were 3.3% (502/15,071) and 1.9% (292/15,071), respectively. Among all cases of rifampicin resistance, 31.7% (159/502) were RMR-TB and 10.2% (51/502) were RR-TB. Multivariable logistic regression analyses revealed that younger age, foreigners, and prior tuberculosis history were significantly associated with MDR/RR-TB. Conclusion Rapid identification of rifampicin resistance targeting the high-risk populations, such as younger generations, foreign-born individuals, and previously treated patients are necessary for patient-centered care.